Desempenho de ligações duplas parafusadas de Pinus sp. submetidas a efeito de temperatura - Geraldi, Andreza (2017)
This work evaluates, experimentally, the residual performance of double joints of Pinus sp. after being submited to temperatures between 200ºC and 300ºC with subsequent cooling. The material description was carried out with tests of moisture content and strength parallel to the grain, following the NBR 7190:1997 conditions. To determine the joints’ strength, specimens with two bolts and double shear were made. Six connections’ treatments were defined: natural wood, oven dried wood, and wood exposed to high temperature during four exposure times: half hour, one hour, one hour and a half, and three hours. The connections were subjected to the compression test, with the load being evaluated for a 10 mm displacement and for rupture. The Pinus sp. wood showed strength parallel to the grain in natural state of 79.03 kN and in the dried state of 131.14 kN. The mean connections resistance in natural state was 37.84 kN and in the dried state it was 47.05 kN. When subjected to high temperature, the connections showed mean resistance of 48.95 kN, 49.26 kN, 33.93 kN and 26,34 kN, for exposure times of half hour, one hour, one hour and a half, and three hours, respectively. The strength peak was obtained after one hour of heating, when the residual resistance overcame the resistance in natural state in 30.18%. The strengths obtained experimentally were compared to the estimates of the Brazilian (NBR 7190:1997) and the European (Eurocode 5:2004, part 1-1) wood structures scaling standards, which presented conservative values, its estimates were even inferior to the lowest strength obtained experimentally, of the three hours heating. The results presented that, despite the exposure to the high temperatures influence on the connections performance, the standards have big safety margin, even in fire situations.